Teknologi Tepat Guna Untuk Meningkatkan Kapasitas Produksi serta Kesehatan Lingkungan Di UKM Jamur Raya - Purwanto, Yuli; Sukmawati, Paramita Dwi; Kumalasanti, Rosalia Arum (LPPM IST AKPRIND Yogyakarta, 2022)
In the village of Gesikan, Subdistrict of gantiwarno, Regency of Klaten, there is a home industry in the form of mushroom cultivation. Mushroom SME in Gesikan Village was established 9 years ago and is still capable of meeting the needs of the food industry. Jamur Raya SME has several types of mushrooms that are cultivated such as oyster mushrooms, straw mushrooms, ear mushrooms, Lingzhi mushrooms and so on. Jamur Raya SMEs carry out production starting from nurseries to ready for planting. The results of these mushroom seeds are usually sold to farmers up to 1000 mushroom seeds every month. A portion of the seedling will be planted on its own and then sold according to customer needs. Mushroom Raya SMEs have a fairly high potential in production in the food industry, but there are also obstacles that are felt by these SME producers.Some of these obstacles are the lack of ability of Mushroom Raya SME to meet consumer needs caused by the limitations of production tools that are still simple/manual. The filling of planting media in the form of baglog and mixing of planting media is still done manually, so it takes a lot of time and energy to process it. In addition, there are environmental constraints, namely in the form of former planting media waste that accumulates, resulting in an unhealthy environment. Another perceived obstacle is from the marketing side which is still conventional or offline. Of course, this also needs to be supported by qualified human resources. Appropriate technology in the form of baglog filling equipment, planting media mixer & straw chopper is expected to be a solution to accelerate mushroom production in meeting consumer needs. Baglog waste treatment in improving environmental quality is also expected to provide solutions to maintain environmental health & cleanliness by using brisket maker and composter. Mushroom Raya SMEs are also expected to survive in the dynamics of the global market so that online marketing is an option to maintain this food industry. Marketing using website media is expected to be able to provide wider information in all circles of society.